Antimicrobial resistance, Virulence profiles of Salmonella enterica serovar Typhimurium isolated from diarrheal children in Thi-Qar province during 2015 - B.Saleh , Manal; K. Hanan, Zaman; H. Mezal , Ezat (University of Thi-Qar Journal of Science, 2019)
A total of 14 Salmonella enterica serovar (ser.)Typhimurium isolates were isolated from diarrheal children in Thi-Qar province during 2015.these isolates were subjected to testing and analyzed for antibiotic resistance and virulence genes by using PCR all isolates were sensitive to the Amikacin and Gentamycin, while three isolates resistance to chloramphenicol, and nalidixic acid and one isolates was resistance to Ciprofloxacin in addition to four isolates were resistance to Ampicillin. All isolates were positive for invA and sipB genes, eight isolates were positive to sopB gene as and only three isolates were positive to spvB gene. These results suggest that S. Typhimurium from clinical is virulent and able to cause salmonellosis in human and it may contribute to pathogenesis. This article is a part of master thesis.